Increased heart rhythm in response to high-dose intravenous methylprednisolone pulse therapy of moderate-to-severe Graves’ orbitopathy - Gutowska, Klaudia; Wojdyńska, Zuzanna; Szewczyk, Sebastian; Milczarek-Banach, Justyna; Miśkiewicz, Piotr (Journal of Medical Science, 2023)
Background. Intravenous glucocorticoids pulses administration is the main therapeutic option in the treatment of Graves’ orbitopathy. Such therapy could relate to the multiple adverse effects. The aim of the study is evaluation the influence of intravenous methylprednisolone (IVMP) pulse therapy on the heart rhythm (HR) changes in patients with active, moderate-to-severe Graves’ Orbitopathy (GO).Methods. We studied 20 patients with moderate-to-severe GO. All patients received 12 IVMP pulses (6x500 mg plus 6x250mg) at equal time intervals in a weekly schedule. We performed Holter ECG monitoring for 3 consecutive days (the day before, the day of IVMP and day after IVMP) to monitor HR and arrhythmias. We compared changes in HR between these 3 days and set time interval when the alteration was significant. This evaluation was performed during the 1st, 6th and 12th IVMP pulse.Results. Increased HR, in comparison with the day before, was registered on the day of IVMP administration. The most significant increase in HR started 5 hours (h) after a pulse administration and lasted 12 h. There were no significant differences in HR between the day before and the day after IVMP. We did not notice any major adverse cardiac events including severe arrhythmias.Conclusions. IVMP therapy is associated with increased HR, that occurs a few hours after infusion, lasts several hours and is transient.